ANALISIS ATAS PENGHITUNGAN PENGHASILAN KENA PAJAK SEBAGAI DASAR PENENTUAN BESARNYA PAJAK PENGHASILAN TERUTANG OLEH PT SAM - Saputro, Mulyo; Djoko Susilo, Danang; Eliza, Eliza; Dariansyah, Deddy (Ekonomi & Bisnis, 2025)
Abstract This study discusses Taxable Income as a basis for calculating the amount of tax payable by PT SAM in 2022. This research is motivated by the difference in revenue and cost recognition between commercial and fiscal. The purpose of this study is to analyze whether PT SAM has calculated Taxable Income in accordance with tax laws and regulations, to find out the obstacles faced and the efforts made to overcome these obstacles. This research uses descriptive analysis method, data collection techniques with literature study, interviews and field studies. The results of this study indicate that the calculation of Taxable Income as a basis for determining the amount of Income Tax payable is not fully in accordance with applicable regulations, the obstacles faced by the company are the lack of human resources who have a background in taxation, resulting in a lack of understanding of tax regulations. Keywords: Fiscal Reconciliation, Taxable Income, Income Tax Payable.